2003
DOI: 10.1046/j.1464-5491.2003.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of KATP channel modulators on counterregulatory responses and cognitive function during acute controlled hypoglycaemia in healthy men: a pilot study

Abstract: Single doses of pharmacological agents which alter membrane KATP channel activity do not affect the counterregulatory response to hypoglycaemia but may modify cognitive function during cerebral glucopenia. The unexpected effects of glibenclamide on cortical function suggest a novel action of sulphonylureas that warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
0
24
2
Order By: Relevance
“…Diazoxide, given orally, suppressed basal C-peptide and suppressed the glucagon response to hypoglycemia induced 2 h later while having no effect on epinephrine, norepinephrine, or neurogenic symptoms (41). Similarly, Bingham et al (42) reported no effect of oral diazoxide (5 mg/kg) on the hormonal counterregulatory response in 10 nondiabetic humans. In our rodent study, diazoxide given intravenously 30 min before hypoglycemia also suppressed C-peptide but resulted in an amplified epinephrine response during hypoglycemia.…”
Section: Discussionmentioning
confidence: 94%
“…Diazoxide, given orally, suppressed basal C-peptide and suppressed the glucagon response to hypoglycemia induced 2 h later while having no effect on epinephrine, norepinephrine, or neurogenic symptoms (41). Similarly, Bingham et al (42) reported no effect of oral diazoxide (5 mg/kg) on the hormonal counterregulatory response in 10 nondiabetic humans. In our rodent study, diazoxide given intravenously 30 min before hypoglycemia also suppressed C-peptide but resulted in an amplified epinephrine response during hypoglycemia.…”
Section: Discussionmentioning
confidence: 94%
“…Bingham et al (43) found no significant effect of diazoxide on the glucagon response to hypoglycemia in healthy men, although the mean peak glucagon concentration tended to be lower after diazoxide than after placebo administration. However, they used a lower dosage of diazoxide and did not document an effect of the drug on insulin secretion by measuring plasma C-peptide concen- Data are means Ϯ SE.…”
Section: Discussionmentioning
confidence: 99%
“…Finger tapping test A computer key was pressed as many times as possible for 10 s. The test was repeated three times at each defined time-point and the mean calculated [10].…”
Section: Methodsmentioning
confidence: 99%